LncRNA GAS5 alleviates rheumatoid arthritis through regulating miR-222-3p/Sirt1 signalling axis - Zhou Yang; Shu-Dian Lin; Feng Zhan; Ying Liu; Yu-Wei Zhan (Taylor & Francis Group, 2021)
Introduction Rheumatoid arthritis (RA) is an autoimmune disease that affects millions of people. Fibroblast-like synoviocytes (FLSs) located in rheumatoid panni play a pivotal role in the formation of RA. The long noncoding RNA (lncRNA) GAS5 is reportedly downregulated in rheumatoid arthritis. However, its detailed mechanism in RA remains to be explored. This study investigated the roles and related mechanisms of GAS5 in RA. Methods The expression levels of GAS5, miR-222-3p, and sirtuin 1 (Sirt1) were evaluated by quantitative PCR (qPCR). Cell proliferation was analyzed by CCK-8 and BrdU assays. Cell apoptosis was assessed by flow cytometry and western blotting. Enzyme-linked immunosorbent assay (ELISA) was utilized to evaluate the levels of TNF-α, IL-1β, and IL-6. The interaction between GAS5 or Sirt1 and miR-222-3p was predicted by starBase and validated by dual-luciferase reporter assay. Results GAS5 expression was found to be downregulated in the serum samples of RA patients and in RA-FLSs. GAS5 overexpression or the inhibition of miR-222-3p impeded the activity of RA-FLSs by repressing their proliferation and inflammation and by promoting apoptosis. Mechanistically, GAS5 indirectly regulates Sirt1 expression by binding miR-222-3p. Further experiments confirmed that Sirt1 overexpression restored the anti-RA activity of GAS5 under miR-222-3p mimic. Conclusions The miR-222-3p/Sirt1 axis was found to be critical for the function of GAS5 in regulating the proliferation, inflammation, and apoptosis of RA-FLSs. These data indicate GAS5 activation as a potential therapeutic strategy for RA progression.